2013
DOI: 10.1309/ajcpuaggb4url5xo
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorescent Method (PLT-F) on Sysmex XN2000 Hematology Analyzer Achieved Higher Accuracy in Low Platelet Counting

Abstract: The new PLT-F method demonstrated excellent results for reproducibility in samples with platelet counts less than 50 × 10(9)/L. PLT-F could be helpful in making better decisions for platelet transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 15 publications
5
53
2
Order By: Relevance
“…These results indicate that a more accurate estimation of platelet counts can be achieved using the XN-2000 PLT-F method, with a reduction of bias (0.7×10 9 /L) than using the XE-2100 PLT-O method, as measured by comparison with the CD41/CD61 IRM of flow cytometry. These results support the conclusion of a previous study which reported that the XN-2000 PLT-F method could be more useful than the XN-2000 PLT-O method for accurate platelet counting in thrombocytopenic samples (N=37, platelet counts <50.0×10 9 /L) [1]. In the present study, platelet counts measured using the XN-2000 PLT-F method were compared with those measured using the XE-2100 PLT-O method in 48 samples with platelet counts less than 20.0×10 9 /L.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…These results indicate that a more accurate estimation of platelet counts can be achieved using the XN-2000 PLT-F method, with a reduction of bias (0.7×10 9 /L) than using the XE-2100 PLT-O method, as measured by comparison with the CD41/CD61 IRM of flow cytometry. These results support the conclusion of a previous study which reported that the XN-2000 PLT-F method could be more useful than the XN-2000 PLT-O method for accurate platelet counting in thrombocytopenic samples (N=37, platelet counts <50.0×10 9 /L) [1]. In the present study, platelet counts measured using the XN-2000 PLT-F method were compared with those measured using the XE-2100 PLT-O method in 48 samples with platelet counts less than 20.0×10 9 /L.…”
supporting
confidence: 90%
“…The recently launched hematology autoanalyzer Sysmex XN-2000 (Sysmex, Kobe, Japan) provides a new method (PLT-F method) for platelet counting based on a fluorescent RNA staining dye named oxazine [1, 2]. The main advantage of the XN-2000's PLT-F method over the former instrument XE-2100's optical method (PLT-O method) is the ability to identify apoptotic white cells and not count them as platelets [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now part of the fluorescent platelet assay, which uses a proprietary oxazine-based dye for staining RNA. Still, IPF is derived from the forward scatter (cell size) versus sideward fluorescence (RNA content) scatterplot [56,57], as shown in Figure 2B. The moderate correlation in IPF between XE-2100 and XN is explained, at least partially, by reduced interference in the XN system [56].…”
Section: Immature Platelet Methodssysmex Hematology Analyzersmentioning
confidence: 99%
“…To the Editor, Platelet count is an important parameter to evaluate hemostatic status for clinical decision making [1,2] that is routinely offered by automated blood cell counters [3]. Many factors can influence its accuracy, e.g.…”
mentioning
confidence: 99%